2017
DOI: 10.1371/journal.pone.0176664
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing of a consanguineous family identifies the possible modifying effect of a globally rare AK5 allelic variant in celiac disease development among Saudi patients

Abstract: Celiac disease (CD), a multi-factorial auto-inflammatory disease of the small intestine, is known to occur in both sporadic and familial forms. Together HLA and Non-HLA genes can explain up to 50% of CD’s heritability. In order to discover the missing heritability due to rare variants, we have exome sequenced a consanguineous Saudi family presenting CD in an autosomal recessive (AR) pattern. We have identified a rare homozygous insertion c.1683_1684insATT, in the conserved coding region of AK5 gene that showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Genome-wide association studies have identified a large number of non-HLA genes associated with CD, such as those coding for cytokines, chemokines and their receptors, cell adhesion molecules, and T- and B-cell activators. [ 32 33 34 35 36 ] The high consanguineous marriage rate in the Saudi community (40–60%)[ 6 37 ] and the clustering of CD cases in certain families are important reasons to conduct genome-wide association studies in Saudi Arabia. These studies would enhance the identification of new non-HLA genetic loci, which could shed light on new genes and genetic pathways involved in disease pathogenesis, and the possibility of a monogenic-form of CD could be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have identified a large number of non-HLA genes associated with CD, such as those coding for cytokines, chemokines and their receptors, cell adhesion molecules, and T- and B-cell activators. [ 32 33 34 35 36 ] The high consanguineous marriage rate in the Saudi community (40–60%)[ 6 37 ] and the clustering of CD cases in certain families are important reasons to conduct genome-wide association studies in Saudi Arabia. These studies would enhance the identification of new non-HLA genetic loci, which could shed light on new genes and genetic pathways involved in disease pathogenesis, and the possibility of a monogenic-form of CD could be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic etiology of CeD is so far widely studied by different genetic approaches like candidate gene sequencing, exome sequencing, SNP genotyping and epigenetic screening 16,[19][20][21][22] . However, compared to the above-mentioned genotyping approaches, there are very few gene expression studies which have assessed the contribution of genes to the pathophysiology of CeD.…”
mentioning
confidence: 99%
“…41 Studies investigating cancer susceptibility within families have suggested genetic links to an array of malignancies at the population level. 14,[142][143][144] Genetic screening offers increased monitoring and surveillance of those with a risk of cancer, in addition to prophylactic, risk-reducing interventions. 144 Fifteen relevant guidelines were developed to provide recommendations on genetic counselling (Supplementary Material) and were in general agreement of the importance of genetic counselling prior to BRCA testing, including breast cancer riskreduction procedures including mastectomy and oophorectomy.…”
Section: Familial Cancer Genetic Counselling Clinic In Saudi Arabiamentioning
confidence: 99%
“…Advances in sequencing technologies, particularly, high throughput sequencing have permitted the discovery of novel genes responsible for cancer heritability, facilitating efficient genetic screening. [14][15][16] The major genetic changes in cancer include single nucleotide variants (SNVs); duplications, insertions, or deletions; exon and gene copy number changes; and structural variants (SVs). 17 The molecular profiling of heritable cancer genes ranges from simple assessments of known hotspot mutations in single genes, to more complex tests that simultaneously detect all gene alterations using allele-specific PCR, Sanger sequencing, multiplex ligation-dependent probe amplification (MLPA), pyrosequencing or mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation